Penggunaan Model Contextual Teaching and Learning untuk Meningkatkan Hasil Belajar Bahasa Indonesia di SDN 7 Sambelia - Lia Rismawati; Wahidatul Murtafi'ah; Muh. Jaelani Al-Pansori (Lembaga Bale Literasi, 2024)
The aim of this research is to describe the improvement in student learning outcomes in learning using Contextual Teaching and Learning assisted by image media. Data collection methods were carried out using quantitative and quantitative methods. Data display techniques are carried out using observation and documentation techniques. Assessment instruments include written tests, observation sheets, and videos of learning activities. The conclusion of this research is the results of data collection on completion, every week the first and second increases, the first 62.5, and the second 82.08. When KKM measures the academic achievement of students who take daily tests, the progress of elementary school graduates is an average of 58.33 students, and only three students improve on daily tests, for example six students who take an average of 62.5 students increase by 50%. and second. by 50%. cycle average 82.08, an increase of 50% across twelve graduates. Overall student achievement was observed in Stage One (50%) and increased to 100% in stage B. Previous results showed that SOL activities improved learning and academic presentation grade 4 students SDN 7 Sambelia Lombok Timur. The conclusion from the results of this research is that through the CTL approach teacher abilities, student activities and student learning achievement increase.